2007
DOI: 10.1007/bf02879925
|View full text |Cite
|
Sign up to set email alerts
|

Risk compensation and vaccination: Can getting vaccinated cause people to engage in risky behaviors?

Abstract: We found some evidence of regression (protective behaviors dropping, after vaccination, to levels reported by the unvaccinated cohort). However, we did not find disinhibition (exceeding the risk taking of the unvaccinated cohort), the greater threat to public health. Although we will not know for several years what effect HPV vaccination has on other behaviors, if any, data on other vaccinations can offer critically important information in the interim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
90
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 12 publications
5
90
0
Order By: Relevance
“…Other factors such as number of sexual partners were not different between the two groups suggesting that vaccination does not affect these sexual issues, a finding that has been consistent in most studies [11,19].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Other factors such as number of sexual partners were not different between the two groups suggesting that vaccination does not affect these sexual issues, a finding that has been consistent in most studies [11,19].…”
Section: Discussionsupporting
confidence: 80%
“…Other factors have been cost and availability, fears of side effects, the attitude of the parents towards vaccination and a history of HPV related disease in family or friends [11]. In our cohort the vaccinated group had less knowledge on HPV infection and believed that condom can largely prevent it.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…19 However, studies have not found that vaccination against other infectious agents increases behavioral disinhibition or risky behaviors. 20 The present study, to our knowledge, is among the first to examine specific factors associated with support to or opposition to required school-entry provision of HPV vaccine among parents of female adolescents eligible for HPV vaccine. Additional study strengths include a large sample size and a focus on women achieved uptake rates for the 3-dose HPV vaccine series on the order of 70-80% within the first year.…”
mentioning
confidence: 92%
“…In a series of important papers [11,28] Blower and her collaborators demonstrated that risk behavior change, in the context of HIV vaccinations, could lead to perverse outcomes. Subsequently, several independent studies have confirmed this phenomenon of perversity in the use of HIV vaccines and anti-virals, and vaccines for the human papillomavirus (HPV) [44,9,50,47,42,46,25,41,29,31,38,5]. …”
mentioning
confidence: 92%